Bone development in laboratory mammals used in developmental toxicity studies. Issue 15 (19th June 2018) - DeSesso, John M.; Scialli, Anthony R.
Abstract : Evaluation of the skeleton in laboratory animals is a standard component of developmental toxicology testing. Standard methods of performing the evaluation have been established, and modification of the evaluation using imaging technologies is under development. The embryology of the rodent, rabbit, and primate skeleton has been characterized in detail and summarized herein. The rich literature on variations and malformations in skeletal development that can occur in the offspring of normal animals and animals exposed to test articles in toxicology studies is reviewed. These perturbations of skeletal development include ossification delays, alterations in number, shape, and size of ossification centers, and alterations in numbers of ribs and vertebrae. Because the skeleton is undergoing developmental changes at the time fetuses are evaluated in most study designs, transient delays in development can produce apparent findings of abnormal skeletal structure. The determination of whether a finding represents a permanent change in embryo development with adverse consequences for the organism is important in study interpretation. Knowledge of embryological processes and schedules can assist in interpretation of skeletal findings.